An Examination of Vertical Synchronization in the Implementing Regulations of the Public Service Law - Sumaya, Ira (Universitas Sumatera Utara, 2025)
Ideally, every legal provision enacted by an authorized state institution should be implemented effectively to regulate public life. In Indonesia, inconsistencies in the enforcement of legal provisions are largely due to the proliferation of regulations that are often overlapping and unsynchronized. This article aims to examine the extent of vertical synchronization between Law Number 25 of 2009 on Public Services and its implementing regulations, from their enactment to the present. This study employs a normative juridical method using a statutory approach. The data are analyzed through the examination of positive law, supported by legal interpretation, analogy, and principles. The findings reveal a lack of vertical synchronization between Law Number 25 of 2009 and its implementing regulations. Several implementing regulations are not aligned with existing legal frameworks; their functions and hierarchical positions do not conform to Indonesia’s legislative structure and legal principles.